1989
DOI: 10.1073/pnas.86.19.7571
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory activity of peptides related to platelet factor 4.

Abstract: Platelet factor 4 (PF4), a secreted platelet protein, alleviates concanavalin A-induced immunosuppression in mice. We now rind that activity also resides in (i) the C-terminal tridecapeptide of PF4 (P13S), (ii) an analog of this in which arginine replaces the lysine residues and in which the last two amino acids are absent, (iii) the C-terminal 18 amino acids of low-affmity platelet factor 4, which is very similar to P13S, and (iv) peptide fragments of P13S that contain only 5-9 amino acids. P13S treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
2

Year Published

1990
1990
1997
1997

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 16 publications
0
18
0
2
Order By: Relevance
“…The immunoregulatory effects of mouse PF4, native and recombinant human PF4 (rPF4), and synthetic C-terminal peptides of human PF4 have been described by our group (18,(95)(96)(97)(98)(99)(100)(101)(102) and others (46,103).…”
Section: Immunoregulationmentioning
confidence: 97%
“…The immunoregulatory effects of mouse PF4, native and recombinant human PF4 (rPF4), and synthetic C-terminal peptides of human PF4 have been described by our group (18,(95)(96)(97)(98)(99)(100)(101)(102) and others (46,103).…”
Section: Immunoregulationmentioning
confidence: 97%
“…Alternatively, the ot-helical tail has been proposed to significantly contribute to the binding with the IL-8 receptor(s) and to confer ligand specificity (8,9). This possibility is based on the observations that a C-terminal tridecapeptide of PF4 has both chemotactic and immunoregulatory activities (43). This observation is in contrast with the finding that IL-8 truncated of its C-terminal at helix and onward into the , sheet remained active (7).…”
mentioning
confidence: 99%
“…Chemokines are cationic and bind heparin. The interaction with heparin and related glycosaminoglycans (GAGs), however, has been thoroughly studied for platelet factor 4 only (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…It has been demonstrated that platelet factor 4 binds to GAGs through its C-terminal a-helix (5)(6)(7), and this led to the suggestion that IL-8 interacts with heparin and heparan sulfate at the same site (15). In this paper, we show that the capacity of IL-8 to bind heparin decreases markedly with progressive shortening of the a-helix, and we present evidence for a functional role of heparan sulfate and heparin as enhancers of IL-8 activity.…”
mentioning
confidence: 99%